2021
DOI: 10.1016/j.cjco.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Oral Anticoagulants Among Patients With Atrial Fibrillation: A Prospective Observational Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“… 12 Our study found that 52.6% of patients were satisfied with the anticlot treatment, which is similar to the satisfaction level reported in Sudanese patients (50.5%), 27 but lower than the Saudi Arabian study's report (63.7%). 12 Regarding ACTS subscale scores, the mean ACTS burden score was lower than that reported in studies conducted in Canada, Japan, and Saudi Arabia 17 , 40 , 41 among patients receiving warfarin therapy. Conversely, a higher ACTS benefit score was reported in our study when compared with the same studies, but was consistent with the Saudi study (11.74 ± 2.43 vs 11.92 ± 2.4).…”
Section: Discussionmentioning
confidence: 65%
“… 12 Our study found that 52.6% of patients were satisfied with the anticlot treatment, which is similar to the satisfaction level reported in Sudanese patients (50.5%), 27 but lower than the Saudi Arabian study's report (63.7%). 12 Regarding ACTS subscale scores, the mean ACTS burden score was lower than that reported in studies conducted in Canada, Japan, and Saudi Arabia 17 , 40 , 41 among patients receiving warfarin therapy. Conversely, a higher ACTS benefit score was reported in our study when compared with the same studies, but was consistent with the Saudi study (11.74 ± 2.43 vs 11.92 ± 2.4).…”
Section: Discussionmentioning
confidence: 65%
“…European Patient Survey in Atrial Fibrillation (EUPS-AF), conducted prior to the approval and widespread uptake of direct thrombin and factor Xa inhibitors, found high patients’ satisfaction with their care: 85.5% of patients rated the quality of care on a five-point Likert scale as good, very good, or excellent [ 49 ]. A recent study demonstrated mixed effects of atrial fibrillation treatment choice, with higher satisfaction in patients on direct oral anticoagulants in unadjusted analysis and higher satisfaction in patients on vitamin K antagonists in covariate-adjusted analysis [ 50 ]. In Lithuania, most patients with atrial fibrillation use warfarin; therefore, they have to visit a PHC centre for coagulation tests once a month.…”
Section: Discussionmentioning
confidence: 99%
“… 87 As well as requiring frequent monitoring and dose adjustments, to ensure appropriate INRs, VKAs also interact with other drugs and certain foods, which can increase bleeding risk and effectiveness, making for complicated therapeutic and dietary regimes for elderly patients, who are often taking many other medications. 88 , 89 These factors have been shown to be linked to reduced patient satisfaction with their OAC treatment 90 which in turn leads to inadequate adherence to VKAs and subsequently poorly anticoagulated patients. 91 In one study, adherence, defined as being greater than 80% was recorded in 51.2% of patients after one year of being prescribed VKAs, following an AF diagnosis.…”
Section: Oral Anticoagulantsmentioning
confidence: 99%